Regeneration of Rabbit Auricular Cartilage After the Intravenous Stem Cell Injection - Virych, Pavlo; Shuvalova, Nadiia; Karas, Anton; Karas, Galina; Chaika, Svitlana; Kucherenko, Tetiana; Minina, Ganna; Timchenko, Marina; Melnykov, Oleg; Minin, Yurii (Acta medica Lituanica, 2023)
Background. The restoration of auricular cartilage is a major problem of otolaryngology. The low regenerative capacity of cartilage requires alternative approaches such as cell and tissue engineering. Stem cells are one of the ways to repair auricular cartilage damages. The aim of the investigation was the regeneration of an artificial defect of the auricular cartilage of rabbits after the intravenous injection of stem cells. Materials and Methods. The study was carried out on rabbits. A narrow strip of auricular cartilage was surgically removed. A previously prepared suspension of homologous mesenchymal stem cells (5 million) in 0.5 ml physiological solution was injected into the vein of the opposite ear. Tissue samples from the site of the injury were collected after 1, 2, and 3 months. Histological examinations of the tissues were carried out after staining with fuchsin-eosin, azure II–eosin, and according to Weigert. In addition, the amount of interleukin-6 (IL-6) and the transforming growth factor β1 (TGF-β1) in the blood serum were determined. Results. The main method of healing is the formation of a connective tissue scar. Yret, an increase of the number of fibroblasts and single islands of the newly formed auricular cartilage was found, which indicates the migration of the injected stem cells to the site of the damage and settling there. The intravenous injection of stem cells did not affect the secretion of pro-inflammatory IL-6, but significantly increased the amount of TGF-β1. Conclusions. We assume that regenerative processes were stimulated. Nevertheless, they were aimed at quickly restoring the tissue integrity through the typical stages of scar formation. The restoration of cartilage integrity requires additional regulatory factors which will determine the chondrogenic differentiation of stem cells.